Maskandi: A critical discourse analysis of indigenous isiZulu songs. Issue 2 (30th June 2016) - Ntombela, Sipho Albert
Abstract: Although different researchers have written various papers about metaphors, very little is known about ways in which a maskandi group called Shwi noMtekhala uses metaphor to convey very sensitive messages and culturally appropriate rhetorical expressions. This study reports on Shwi noMtekhala's conveyance of a sensitive message, in a song entitled 'Ubuhle Bakhe', from a critical discourse analysis perspective and then draws inferences on how this indigenous musical genre can be a tool for reading literacy instruction among early readers. I chose to analyse this particular song as a representative of maskandi groups which use imagery, as well as other musical expressions, to convey very sensitive messages. The main finding of the analysis is that the reported song reveals a number of sociocultural themes relating to ways of knowing in indigenous literacy systems. These include use of metaphoric expressions, call-and-response patterns, repetition, indirection, interactive and group dynamics that are general, yet particular, to the isiZulu maskandi tradition. Different from what previous research found about the aesthetics of this music group, I have shown that its principles can be used for literacy instruction among early readers. In the end, implications for using indigenous music systems and their resultant pedagogical strategies are considered for adaptation in classrooms.